Neurophysiological evidence of an association between cognitive control and defensive reactivity processes in young children. (October 2015) - Lo, Sharon L.; Schroder, Hans S.; Moran, Tim P.; Durbin, C. Emily; Moser, Jason S.
Highlights: ERN, Pe, startle reflex, and parietal asymmetry were measured in young children. Reduced ERN was related to a larger startle and greater right parietal activity. Age predicted smaller startle, larger ERN, and better behavioral performance. Age did not moderate the association between ERN and startle. Age did not moderate the association between ERN and parietal asymmetry. Abstract: Interactions between cognitive control and affective processes, such as defensive reactivity, are intimately involved in healthy and unhealthy human development. However, cognitive control and defensive reactivity processes are often studied in isolation and rarely examined in early childhood. To address these gaps, we examined the relationships between multiple neurophysiological measures of cognitive control and defensive reactivity in young children. Specifically, we assessed two event-related potentials thought to index cognitive control processes – the error-related negativity (ERN) and error positivity (Pe) – measured across two tasks, and two markers of defensive reactivity processes – startle reflex and resting parietal asymmetry – in a sample of 3- to 7-year old children. Results revealed that measures of cognitive control and defensive reactivity were related such that evidence of poor cognitive control (smaller ERN) was associated with high defensive reactivity (larger startle and greater right relative to left parietal activity). The strength of associations between the ERN and measures of defensive reactivity did not vary by age, providing evidence that poor cognitive control relates to greater defensive reactivity across early childhood years.